The big finish - Hall, James W. (James Wilson), 1947- (A Thorn novel, 2014)
"A year ago Thorn's son, Flynn Moss, disappeared into the eco-underground, his only contact with Thorn a series of postcards chronicling his exploits. But a postcard arrives unlike the others, a call for help, Thorn jumps into action, setting off for North Carolina. But before Thorn arrives, he's intercepted by a federal agent who informs him he's too late--Flynn had been acting as an informant for the FBI, and when his traitorous acts were discovered, he was summarily executed. The agent proposes a scheme to catch Flynn's killer using Thorn as bait.